2017
DOI: 10.4317/jced.53679
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of diode laser against acyclovir cream for the treatment of herpes labialis

Abstract: BackgroundRecently alternative therapies such as the use of diode laser therapy have been introduced for recurrent herpes labial infection. The aim of this study was to evaluate the effectiveness of diode laser for treatment of recurrent herpes labialis.Material and MethodsThis was single-blind randomized clinical trial to evaluate the efficacy of diode laser for the treatment of recurrent herpes labial. In total, 60 patients whit recurrent herpes simplex labialis were selected and randomly divided in to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…Moreover, such drugs should be administered many times on consecutive days and may not only interact with other medications but also increase the risk of nephrotoxicity-especially the systemic ones. 7 For immunocompromised patients, however, the treatment is based on systemic drugs for periods between ten days and up to a year. Clinicians should thus monitor the patients since lesions that have not healed within 7-10 days need to be either recultured or biopsied, and sensitivity tests should also be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such drugs should be administered many times on consecutive days and may not only interact with other medications but also increase the risk of nephrotoxicity-especially the systemic ones. 7 For immunocompromised patients, however, the treatment is based on systemic drugs for periods between ten days and up to a year. Clinicians should thus monitor the patients since lesions that have not healed within 7-10 days need to be either recultured or biopsied, and sensitivity tests should also be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Um ponto a ser destacado é a divergência de protocolos de tratamento para herpes simples labial quanto aos parâmetros do laser em si, tanto para a TFD como para a terapia de fotobiomodulação (FBM) no período de reparo da lesão, e dos benefícios da associação ou não das duas terapias; esses fatos dificultam a comparação entre estudos. [10][11][12] O que se sabe é que nenhum tratamento a laser é capaz de eliminar completamente o vírus e a sua recorrência. Entretanto, diminui a dor e o intervalo de recorrência, sem causar qualquer efeito secundário, e a TFD reduz a carga viral na fase de vesícula do herpes 3,5 .…”
Section: Discussionunclassified
“…At present, many experiments have confirmed the promoting effect of laser on the treatment of oral mucositis. Honarmand et al found that semiconductor laser treatment shortened the recovery time and relieved the pain severity of RHL patients [ 44 ]. Sanchez et al found that compared with acyclovir cream and tablets, laser treatment has fewer side effects and prolongs the recurrence time [ 45 ].…”
Section: Removal Of Hyperplastic Gum Tissuementioning
confidence: 99%